BETWEEN REALITY AND THE NEEDS: RESPONSIBILITIES OF EDUCATIONAL INSTITUTIONS IN DEVELOPING ARCHIVAL SCIENCE IN INDONESIA - Bramantya, Arif Rahman; Prasetyo, Arif (Record and Library Journal, 2019)
Background of the study: The requirement of Archivists (archivist and records manager) in Indonesia is not equal to the quantity of graduates produced by educational institutions. In addition 4.0 with the educational requirements and the needs of stakeholders who want graduates from the archival field at the highest level should be accommodated. Therefore, educational institutions are forefront in developing archival science.Purpose: This study aims to find out how the responsibility of educational institutions in developing the knowledge of the field of archives in Indonesia in the era of information technologyMethod: This study uses descriptive qualitative, interviews, and literature studies.Findings: This study discusses the Efforts of educational institutions to improve the archival science by establishing a higher education program through the mindset of building and synergy with other elements. In addition, educational institution has responsibility in the archival field in Realizing the archival sense.Conclusion: Archival science more interpreted in a theoretical structure that supports the activities of archival practical, rather than academic disciplines. If the method is applied science, the science of archives will tend to be highly empirical making it a descriptive science. This tendency will make archival science seeks only to gather facts and less attention to the development of the concept as well as demanded by the development of science through a study. To develop scientific archives in Indonesia, the necessary synergy between archival institutions, archival professional associations, educational institutions allied, as well as among students in educational institutions. This must be done with the agreement in the field of archives that apply universally to realize the creation of the organization of archives in Indonesia better.